2011
DOI: 10.1681/asn.2010101072
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Dendritic Cells Induce Innate Immunity against Bacterial Pyelonephritis

Abstract: Dendritic cells (DCs) are the most abundant immune cells in the kidney and form an intricate network in the tubulointerstitium, suggesting that they may play an important role in interstitial infections such as pyelonephritis. Here, we optimized a murine pyelonephritis model by instilling uropathogenic Escherichia coli two times at a 3-hour interval, which produced an infection rate of 84%. By 3 hours after the second instillation, resident kidney DCs began secreting the chemokine CXCL2, which recruits neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 27 publications
8
79
0
Order By: Relevance
“…The DCs in the renal medulla are particularly potent at recruiting neutrophils (40), perhaps because they are the first to encounter the ascending bacteria and/or because of microenvironmental cues that cause them to specialize at anti-infectious functions. Notably, kidney macrophages contributed to neither the chemokine production nor the phagocytosis of uropathogenic E. coli (55). By contrast, another study reported that renal macrophages are critical for the defense against candida (56), which preferentially infect murine kidneys.…”
Section: Defense Against Urogenital Tract Infectionsmentioning
confidence: 96%
“…The DCs in the renal medulla are particularly potent at recruiting neutrophils (40), perhaps because they are the first to encounter the ascending bacteria and/or because of microenvironmental cues that cause them to specialize at anti-infectious functions. Notably, kidney macrophages contributed to neither the chemokine production nor the phagocytosis of uropathogenic E. coli (55). By contrast, another study reported that renal macrophages are critical for the defense against candida (56), which preferentially infect murine kidneys.…”
Section: Defense Against Urogenital Tract Infectionsmentioning
confidence: 96%
“…rMoPh resident at steady state are induced to rapidly produce proinflammatory innate cytokines (TNF, IL-6, and IL-1) and chemokines (CCL2, CCL5, CXCL10, and CXCL2) depending on environmental cues. 40,70,74,76 As a result, Ly6C + monocytes and other leukocytes are recruited into the kidney, providing a secondary and major source of innate mediators. 35,40,74 This innate phase, evident during either glomerular or tubulointerstitial inflammation, shapes subsequent adaptive immune responses by rMoPh, although this progression has been more clearly described for interstitial compared with glomerular rMoPh.…”
Section: Functions Of Rmoph In Immunity Tissue Injury and Tissue Rementioning
confidence: 99%
“…Furthermore, CD11c + kidney cells possess a transcriptome that resembles that of DCs but not of macrophages (8,9). Although kidney DCs have been shown to perform sentinel and regulatory functions in inflammation and infection (10), macrophages contributed to host protection from infection and maintained tissue homeostasis (1,11,12). In contrast, inappropriate macrophage functions promoted fibrosis in various organs (13,14).…”
mentioning
confidence: 99%